2017
DOI: 10.1177/1352458517732843
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of highly active pediatric multiple sclerosis

Abstract: The rate of highly active disease among pediatric MS patients is high; more than 40% in our cohort. Response to NTZ and FTY treatment is similar if not better than observed in adults. Current treatment modalities including earlier treatment initiation and the introduction of NTZ and FTY have significantly improved the clinical course of pediatric MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 19 publications
0
49
0
4
Order By: Relevance
“…A recent German study reported that 41.6% of patients with paediatric-onset multiple sclerosis fulfilled criteria for highly active disease. 32 There was no correlation between disease activity and sex or age at presentation. Lesion load at first MRI and disease activity in the first year can be suggestive of a highly active disease, and thus aid patient selection for the most effective therapies.…”
Section: Clinical Features and Disease Course: Does The Age Matter?mentioning
confidence: 88%
See 4 more Smart Citations
“…A recent German study reported that 41.6% of patients with paediatric-onset multiple sclerosis fulfilled criteria for highly active disease. 32 There was no correlation between disease activity and sex or age at presentation. Lesion load at first MRI and disease activity in the first year can be suggestive of a highly active disease, and thus aid patient selection for the most effective therapies.…”
Section: Clinical Features and Disease Course: Does The Age Matter?mentioning
confidence: 88%
“…When age at onset was treated as a continuous variable, it reversely correlated with relapse rate. A recent German study reported that 41.6% of patients with paediatric‐onset multiple sclerosis fulfilled criteria for highly active disease . There was no correlation between disease activity and sex or age at presentation.…”
Section: Clinical Features and Disease Course: Does The Age Matter?mentioning
confidence: 99%
See 3 more Smart Citations